Hospitalization for self-harm during the early months of the COVID-19 pandemic in France: A nationwide retrospective observational cohort study - Fabrice JOLLANT; Adrien ROUSSOT; Emmanuelle CORRUBLE; Jean-Christophe C; Bruno FALISSARD; Yann MIKAELOFF; Catherine QUANTIN (Elsevier, 2021)
ABSTRACT: Background: Little is known to date about the impact of COVID-19 pandemic on self-harm. Methods: The number of hospitalizations for self-harm (ICD-10 codes X60-X84) in France from 1st January to 31st August 2020 (including a two-month confinement) was compared to the same periods in 2017-2019. Statistical methods comprised Poisson regression, Cox regression and Student's t-test, plus Spearman's correlation test relating to spatial analysis of hospitalizations. Outcomes: There were 53,583 self-harm hospitalizations in France during January to August 2020. Compared to the same period in 2019, this represents an overall 8·5% decrease (Relative Risk [95% Confidence Interval] = 0·91 [0·90-0·93]).This decrease started in the first week of confinement and persisted until the end of August. Similarly, decrease was found in both women (RR=0·90 [0·88-0·92]) and men (RR=0·94 [0·91-0·95]), and in all age groups, except 65 years and older. Regarding self-harm hospitalizations by means category, increases were found for firearm (RR=1·20 [1·03-1·40]) and for jumping from heights (RR=1·10 [1·01-1·21]). There was a trend for more hospitalizations in intensive care (RR=1·03 [0·99-1·07]). The number of deaths at discharge from hospital also increased (Hazard Ratio = 1·19 [1·09-1·31]). Self-harm hospitalizations were weakly correlated with the rates of hospitalization for COVID-19 across administrative departments (Spearman's rho =-0·21; p = 0·03), but not with overall hospitalizations. Interpretation: The COVID-19 pandemic had varied effects on self-harm hospitalizations during the early months in France. Active suicide prevention strategies should be maintained. Funding: French National Research Agency.